Mulberry Transcription Factor MnDREB4A Confers Tolerance to Multiple Abiotic Stresses in Transgenic Tobacco. - Xue-Qin Liu; Chang-Ying Liu; Qing Guo; Meng Zhang; Bo-Ning Cao; Zhong-Huai Xiang; Ai-Chun Zhao (PLoS ONE, 2015)
The dehydration responsive element binding (DREB) transcription factors have been reported to be involved in stress responses. Most studies have focused on DREB genes in subgroups A-1 and A-2 in herbaceous plants, but there have been few reports on the functions of DREBs from the A-3-A-6 subgroups and in woody plants. Moreover, mulberry trees are ecologically and economically important perennial woody plants, but there has been little research on its stress physiology, biochemistry and molecular biology. In this study, a DREB gene from the mulberry tree, designated as MnDREB4A, classified into the A-4 subgroup by our previous study, was selected for further characterization. Our results showed that the MnDREB4A protein was localized to the nucleus where it activated transcription. The promoter of MnDREB4A can direct prominent expression downstream of the β-glucuronidase (GUS) gene under heat, cold, drought and salt stress, and GUS staining was deepest after 12 h of stress treatment. The MnDREB4A-overexpression transgenic tobacco showed the improved growth phenotype under untreated conditions, such as greener leaves, longer roots, and lower water loss and senescence rates. Overexpression of MnDREB4A in tobacco can significantly enhance tolerance to heat, cold, drought, and salt stresses in transgenic plants. The leaf discs and seedlings of transgenic plants reduced leaf wilting and senescence rates compared to the wild type plants under the different stress conditions. Further investigation showed that transgenic plants also had higher water contents and proline contents, and lower malondialdehyde contents under untreated condition and stress conditions. Our results indicate that the MnDREB4A protein plays an important role in plant stress tolerance.